2013
DOI: 10.1097/aap.0b013e31829ecfa6
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Incidence of Suspected Epidural Hematoma and the Hidden Imaging Cost of Epidural Catheterization

Abstract: Introduction Hematoma associated with epidural catheterization is rare, but the diagnosis might be suspected relatively frequently. We sought to estimate the incidence of suspected epidural hematoma after epidural catheterization, and to determine the associated cost of excluding or diagnosing an epidural hematoma through radiologic imaging. Methods We conducted an electronic retrospective chart review of 43,200 patient charts using 4 distinct search strategies and cost analysis, all from a single academic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…While we did not specifically investigate prophylactic dosing regimens, it is also conceivable that residual anticoagulant activity could exist 12 hours following twice-daily dosing strategies, because at this time interval anti-Xa levels have been previously reported to be approximately 50% of peak levels. 8 Given the low incidence of symptomatic epidural hematomas (1.38 per 10,000 epidural blocks; 95% confidence interval, 0-0.002), 21 an increase in the occurrence of this adverse event, secondary to residual enoxaparin activity, could easily go unrecognized and might be challenging to detect in prospective studies. However, the incidence of epidural hematoma formation was recently found to be increased in the setting of abnormal coagulation parameters.…”
Section: Discussionmentioning
confidence: 99%
“…While we did not specifically investigate prophylactic dosing regimens, it is also conceivable that residual anticoagulant activity could exist 12 hours following twice-daily dosing strategies, because at this time interval anti-Xa levels have been previously reported to be approximately 50% of peak levels. 8 Given the low incidence of symptomatic epidural hematomas (1.38 per 10,000 epidural blocks; 95% confidence interval, 0-0.002), 21 an increase in the occurrence of this adverse event, secondary to residual enoxaparin activity, could easily go unrecognized and might be challenging to detect in prospective studies. However, the incidence of epidural hematoma formation was recently found to be increased in the setting of abnormal coagulation parameters.…”
Section: Discussionmentioning
confidence: 99%
“…This FDA recommendation notes that epidural hematoma with significant nerve injury remains a problem despite previous ASRA Guidelines for anticoagulation management. [22][23][24] This step also includes a suggestion to review drug allergies (based on common practice). The original proposal included a review of medical history and DNR status, which were removed based on feedback from the surveys.…”
Section: Discussionmentioning
confidence: 99%
“…The inci-dence of spinal hematoma in non-obstetric EA found in our study (18.5 per 100,000) is consistent with studies including large sample size, which have reported incidences of spinal hematoma in the range of 11-19 per 100,000 catheterizations. 6,12,33,34,36 Our estimates may be more precise (as reflected by the narrow CIs) probably because of our larger sample size. Of note, after excluding patients undergoing vascular procedures, the incidence of spinal hematoma in non-obstetric patients was 14.7 9 10 À5 (95% CI, 12.7 9 10 À5 to 17.0 9 10 À5 ).…”
Section: Discussionmentioning
confidence: 84%